Criminal responsibility of the perpetrator with alternating split personality - Golonka, Anna (Ius Novum, 2023)
The study is devoted to the issue of criminal liability of a perpetrator suffering from conversion identity disorders. Therefore, its aim is to highlight the dilemmas arising from a split personality disorder in the context of the insanity of the perpetrator of a prohibited act. Based on the example of Kenneth Bianchi (case study), the difficulties related to the diagnosis of this disorder and its consequences in relation to criminal liability are shown. In turn, the analytical-dogmatic method is used to consider the issue related to the recognition of these disorders as a specific category of causes of the condition referred to in Article 31 § 1 of the Polish Criminal Code. Regardless of this, the study also presents an approach to this issue that differs from that previously presented in the literature. The conclusions drawn on this basis also allow for filling a certain gap in the Polish literature on criminal law, which is a lack of studies on the subject matter.